2002
DOI: 10.1046/j.1524-4725.2002.02017.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluridil, a Rationally Designed Topical Agent for Androgenetic Alopecia: First Clinical Experience

Abstract: Topical fluridil is nonirritating, nonsensitizing, nonresorbable, devoid of systemic activity, and anagen promoting after daily use in most AGA males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 21 publications
2
20
0
1
Order By: Relevance
“…The 12-month study in male AGA volunteers also demonstrated fluridil's efficacy [Sovak et al, 2002a]. The generally observed cessation of hair loss in most patients and strengthening and regrowth of hair in some patients suggest that daily topically applied 2% fluridil is having some effect on the hair growth cycle.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The 12-month study in male AGA volunteers also demonstrated fluridil's efficacy [Sovak et al, 2002a]. The generally observed cessation of hair loss in most patients and strengthening and regrowth of hair in some patients suggest that daily topically applied 2% fluridil is having some effect on the hair growth cycle.…”
Section: Discussionmentioning
confidence: 80%
“…Residual solvents were measured by GC headspace analysis on an HP 5890 Series II Gas Chromatograph (Hewlett Packard, Palo Alto, CA) with a 30.0 m  0.32 ID DB-1701 capillary column (J&W Scientific, Folsom, CA) by sampling (100 mL) of head space from a sealed 10-mL glass serum vial containing 250 mg of compound, 0.5 mL 1-methyl-2-pyrrolidinone, and 1-butanol internal standard at 1001C. The methods used for clinical assessment of fluridil in human patients including efficacy, safety, systemic absorption, and cumulative irritancy studies are described elsewhere [Sovak et al, 2002a] Compounds (3-amino-2-hydroxy-2-methyl-N-(4-nitro-3-trifluoromethyl)phenyl) propanamide, (BP-34).…”
Section: General Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…30 In FPHL, fluridil 2% solution prevented progression of hair loss and increased hair diameter in an open clinical study. 31 Fluridil is being used throughout Europe, but is still awaiting approval from the Food and Drug Administration (FDA) in the United States.…”
Section: Fluridilmentioning
confidence: 97%
“…58 In a controlled clinical trial, once-a-day Epilobium extract treatment significantly reduced international prostate specific score in male subjects in comparison to placebo treatment over 3 months. 59 Overall, as a botanical source for a novel treatment for AGA, Epilobium species have shown significant potential and warrant further exploration owing to their potent 5α-reductase type II and PGD2 inhibiting activities.…”
mentioning
confidence: 99%